Effect of heat treatment on the tribological performance of electroless quaternary nickel alloy - Zaimi, M.; Azran, M. N.; Kasim, M. S.; Kamal, M. R. M.; Othman, I. S.; Lau, K. T.; Widodo, T. D.; Azizul Helmi, Sofian (Penerbit UMP, 2019)
Heat treatment of nickel-based alloy can increase the alloy’s hardness as well as the wear resistance properties. Nevertheless, the effect of heat treatment on the quaternary Ni alloy coating properties produced from electroless deposition bath is less known due to its composition uniqueness. In this study, Cu and Co are added in the Ni-P alloy matrix using hypophosphite-based Electroless Ni deposition method on mild steel substrate in acidic and alkaline bath. The coatings are then heat treated at 623 K for 3600s. The coatings hardness is measured using microVickers hardness tester and the surface morphology of the coatings are studied using both Scanning Electron Microscope (SEM) and X-ray diffraction (XRD) analysis. X-ray fluorescence (XRF) measurement is used to measure the coatings compositions. The wear behavior of the coatings is also investigated before and after heat treatment using ASTM G-99. The coatings from acidic-based bath produces Ni-Cu-Co-P alloy coating while the alkaline-based bath produces Ni-Co-Cu-P alloy based on XRF analysis. Results show that the hardness increases more than 20% for acidic-based bath and 40% for alkaline-based bath coating. The highest increment is the Ni-Co-Cu-P alloy, from 553.3 HV to 991.3 HV after heat treatment. The grain refinement of the coatings can be observed after heat treatment in SEM observation. This is proved by the XRD measurement results where polycrystalline Ni (111) formation is seen after heat treatment overshadowing the Cu (111) and Co (111) peaks. Ni phosphide species are also formed after the heat treatment. The polycrystalline Ni and the Ni phosphide formation, as well as the existence of Co and Cu in the alloy deposits reduces the wear rate significantly after the heat treatment.